Improvement in lubricating properties of engine oil by blending with palm oil, trimethylolpropane ester and nanoparticles - Rasheed, Hussein Saeed (2019)
Engine oil plays an important role in reducing the friction and wear between the metal parts of an engine and acts as a coolant to lower the engine temperature. Mineral oil has been dominated the market as the base oil for engine oil due to its availability, and good performance. However, due to the decomposition issues and emission of toxic gases during its use, it becomes a source of pollution to the environment. The present study aimed at evaluating the alternative base oil for engine oil which is more environmentally friendly and effective in reducing wear and friction. This is achieved by blending the mineral oil with biodegradable base oils namely palm oil and trimethylolpropane (TMP) ester. The effect of adding nanomaterials on the friction properties were evaluated. The study also investigated the thermal degradation characteristics of the formulated engine oil in air and inert nitrogen.